Integrating art and creativity into business practice - Schiuma, Giovanni; Lerro, Antonio (Business Science Reference, 2017)
"This book brings together high quality academic and applied research on why and how art and creativity may integrate into business practices, influence innovation patterns, new entrepreneurial dynamics and mindsets and value creation capacity of private and public organizations. Including Featuring extensive coverage on relevant topics, such as business model innovation, organizational performance improvement, and entrepreneurial learning"-- Provided by publisher.